Revitalizing Social Solidarity: Addressing the Community Crisis in Meritocratic Societies - Ernestus Holivil; Laurensius Petrus Sayrani; I Putu Yoga Bumi Pradana (Jurnal Ledalero, 2026)
This article examines the crisis of social solidarity in meritocratic societies, which is driven by increasing social inequality and individualism. While meritocracy ideally ensures equal opportunities for all individuals, in practice, it often deepens social disparities and weakens communal bonds. This study aims to explore how the revitalization of social solidarity can serve as a solution to the fragmentation caused by meritocratic systems. Using a theoretical approach based on communitarianism, this article analyzes various strategies to strengthen social ties, such as community engagement, social capital development, and inclusive policy reforms. The findings indicate that social solidarity can be restored through active participation in community activities, increased involvement in broader social networks, and the implementation of policies that balance individual achievements with collective interests. Thus, revitalizing social solidarity is not only essential in addressing the negative impacts of meritocracy but also in fostering a more just and inclusive society.